Advanced practices for care management: reflections on the Brazilian Nursing - João Lucas Campos de Oliveira; Beatriz Rosana Gonçalves de Oliveira Toso; Laura Misue Matsuda
ABSTRACT Objective: to explain about the Advanced Nursing Practice and to discuss the possibilities of the Advanced Practice for the management of nursing care in Brazil. Method: this is a theoretical-reflexive trial, based on the international literature on advanced practices in nursing and analysis relevant to the profession and to the Brazilian context. Results: the object of the study was described in the following driving axes: Advanced Practice Nurse: international examples and Brazilian reality; Reflections on the care management by the Advanced Practice Nurse in Brazil. Autonomy, qualified training, leadership and performance based on scientific evidences as the foundation of the best care management by the Advanced Nursing Practice, stand out. Final considerations: while early and challenging, the work of Brazilian nursing towards advanced professional practice seems to be interesting, since the possibilities of managing the care of this modality of nurses' performance are evident.